2020
DOI: 10.1128/iai.00931-19
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Signal Transduction Systems in the Human Pathogen Streptococcus agalactiae

Abstract: Streptococcus agalactiae (group B Streptococcus [GBS]) is an important cause of invasive infection in newborns, maternal women, and older individuals with underlying chronic illnesses. GBS has many mechanisms to adapt and survive in its host, and these mechanisms are often controlled via two-component signal transduction systems. In GBS, more than 20 distinct two-component systems (TCSs) have been classified to date, consisting of canonical TCSs as well as orphan and atypical sensors and regulators. These sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…The major regulator of host-pathogen interaction in ß-hemolytic streptococci is the transcriptional factor CovR belonging to the PhoP family of bacterial response regulator [19,20]. Targeted analysis in GBS demonstrated that CovR directly represses the transcription of the PLOS GENETICS cyl operon encoding the ß-h/c toxin, the bibA gene, and the PI-1 pili operon [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The major regulator of host-pathogen interaction in ß-hemolytic streptococci is the transcriptional factor CovR belonging to the PhoP family of bacterial response regulator [19,20]. Targeted analysis in GBS demonstrated that CovR directly represses the transcription of the PLOS GENETICS cyl operon encoding the ß-h/c toxin, the bibA gene, and the PI-1 pili operon [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The number of TCSs per species tends to be higher in environmental species that are exposed to fluctuations in the natural environment and that possess larger genomes. Some clinically-significant examples are presented in Table 1 [ 15 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major regulator of host-pathogen interaction in ß-hemolytic streptococci is the transcriptional factor CovR belonging to the PhoP family of bacterial response regulator (18,19). Targeted analysis in GBS demonstrated that CovR directly represses the transcription of the cyl operon encoding the ß-h/c toxin, the bibA gene, and the PI-1 pili operon (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%